Epizootic ulcerative syndrome – First report of evidence from South Africa's largest and premier conservation area, the Kruger National Park. (December 2019) - Malherbe, W.; Christison, K.W.; Wepener, V.; Smit, N.J.
Abstract: This study reports on the first evidence of genomic material of the causative agent for epizootic ulcerative syndrome (EUS), Aphanomyces invadans, from fish in the Limpopo River system and the Kruger National Park, South Africa. Fourteen fish species were collected from various depressions in the floodplains of the Limpopo and Luvuvhu Rivers in the Makuleke Wetlands during 2015 and 2017. A single individual of Clarias gariepinus was found to have a suspected epizootic ulcerative syndrome (EUS) lesion. Samples were collected and evidence of A. invadans DNA in the samples was found through PCR and amplicon sequencing. The spread of EUS into this premier conservation area is of concern as it could potentially spread across borders and into other naïve river systems with important conservation statuses. Graphical abstract: Image 1 Highlights: First evidence of genomic material of Aphanomyces invadans from the Limpopo River. Incidental discovery of A. invadans on Clarias gariepinus in the Makuleke Wetlands. Little information known about the distribution of EUS in northern South Africa.